A common pathway to cancer: Oncogenic mutations abolish p53 oscillations. (October 2022) - Xiong, Lingyun; Garfinkel, Alan
Abstract: The tumor suppressor p53 oscillates in response to DNA double-strand breaks, a behavior that has been suggested to be essential to its anti-cancer function. Nearly all human cancers have genetic alterations in the p53 pathway; a number of these alterations have been shown to be oncogenic by experiment. These alterations include somatic mutations and copy number variations as well as germline polymorphisms. Intriguingly, they exhibit a mixed pattern of interactions in tumors, such as co-occurrence, mutual exclusivity, and paradoxically, mutual antagonism. Using a differential equation model of p53-Mdm2 dynamics, we employ Hopf bifurcation analysis to show that these alterations have a common mode of action, to abolish the oscillatory competence of p53, thereby, we suggest, impairing its tumor suppressive function. In this analysis, diverse genetic alterations, widely associated with human cancers clinically, have a unified mechanistic explanation of their role in oncogenesis. Graphical abstract: p53 oscillations are required for DNA damage response, to facilitate cell cycle arrest and DNA repair, ultimately safeguarding genome integrity. Oncogenic alterations in the p53 pathway abolish p53 oscillations, allowing for cell proliferation with DNA damage and genome instability. Image 1 Highlights: p53 oscillations are essential for DNA damage response in normal physiology. Genetic alterations in the p53 pathway exhibit a puzzling pattern of interactions in tumors. These alterations impact key biophysical parameters of p53-Mdm2 dynamics. Hopf bifurcation analysis reveals a region for sustained p53 oscillations in the multi-parameter space. Diverse genetic alterations abolish the oscillatory competence of p53 to promote cancer.